A pedunculated left ventricular hemangioma initially misdiagnosed as thrombus in a woman with atypical chest pain - ÖZBEN SADIÇ, BESTE (SPRINGER, 2009)
The incidence of cardiac masses increased as echocardiography is becoming increasingly popular. Benign tumors of the heart constitute about 72% of all primary cardiac neoplasms and hemangioma accounts for 5-10% of benign cardiac tumors. Cardiac hemangiomas are generally asymptomatic and diagnosed incidentally during echocardiography or magnetic resonance imaging (MRI). We reported a 52-year-old woman presented with atypical chest pain and exertional dyspnea. The echocardiographic examination revealed a hyperechoic round mass in the left ventricle. With an initial diagnosis of left ventricular thrombus, the patient underwent cardiac MRI. The mass was found compatible with cardiac hemangioma. It was removed surgically and histopathologic evaluation identified a cardiac hemangioma. As reports of cardiac hemangioma are extremely rare and cardiac masses are mostly thought to be thrombi or myxomas (being the most common primary cardiac tumor), such hemangioma cases warrant attention as possibility of hemangioma should also be kept in mind.
Keywords: Cardiac hemangioma; Cardiac thrombus; Cardiac mass; Chest pain; PRIMARY CARDIAC TUMORS; CAVERNOUS HEMANGIOMA; HEART; NEOPLASMS; EXPERIENCE; MIMICKING; CT